Author Correction: Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.
1 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum for (EFR)
Keywords: dept.phy; peer-reviewed